LEARNING INNOVATION: IMPROVING EDUCATIONAL EFFECTIVENESS IN THE DIGITAL AGE - Mustafa, Muhammad; Jasri, Moh; Maulana, Muhammad Zaki (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Abstract:The development of digital technology has had a significant impact on the education sector. Using technology in learning enables innovations to improve the effectiveness of the learning process. This article aims to analyze learning innovations that can enhance the effectiveness of education in the digital era. A literature review was conducted to explore the concept of learning in the digital era, identify the advantages and challenges faced in implementing technology in education, and examine the development of teaching innovations in the digital era. The research method used is a literature review of related research and an analysis of relevant data and findings. The results of this study provide a better understanding of the effectiveness of learning innovations in the digital era. Factors that influence the effectiveness of learning innovations are also analyzed to provide a comprehensive picture of the influence of technology in education. The discussion of this article highlights the effectiveness of learning innovations in the digital era, considering the advantages and challenges that arise. The implications of the findings of this study for learning practices are identified and presented, and relevant recommendations are provided to support the effective use of learning innovations in the context of digital education. This study concludes that learning innovations can improve the effectiveness of education in the digital era. However, it is essential to consider the factors that influence the success of these innovations, such as teacher technological competence, infrastructure availability, and adequate policy support. This article makes an essential contribution to understanding technology use in education and provides a basis for further research in this area.